CARMEN : an initiative for integrated prevention of noncommunicable disaease in the Americas (PAHO Washington, D.C.US, 2003)
Illustrates how CARMEN can facilitate the control of NCDs of major public health importance. Uses health promotion strategies and disease prevention action at the community level, as well as through the health care services, oriented towards the simultaneous prevention of several NCDs by reducing and controlling their shared risk factors.
Keywords: CHRONIC DISEASES